2010
DOI: 10.1177/1745691610369465
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Social Desirability Scales

Abstract: Social desirability (specifically, impression management) scales are widely used by researchers and practitioners to screen individuals who bias self-reports in a self-favoring manner. These scales also serve to identify individuals at risk for psychological and health problems. The present review explores the evidence with regard to the ability of these scales to achieve these objectives. In the first part of the review, I present six criteria to evaluate impression management scales and conclude that they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
135
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(165 citation statements)
references
References 189 publications
(319 reference statements)
14
135
0
7
Order By: Relevance
“…Our findings on social desirability suggest that it is useful to maintain a distinction between impression-management-focused aspects (Uziel, 2010) and lying aspects (as in the EPQ Lie scale). The former are likely to be broadly associated with personality (except Extraversion) in different cultural groups, whereas the latter may have a more circumscribed effect that is more in line with the view of social desirability as response distortion.…”
Section: Instrument Developmentmentioning
confidence: 75%
See 1 more Smart Citation
“…Our findings on social desirability suggest that it is useful to maintain a distinction between impression-management-focused aspects (Uziel, 2010) and lying aspects (as in the EPQ Lie scale). The former are likely to be broadly associated with personality (except Extraversion) in different cultural groups, whereas the latter may have a more circumscribed effect that is more in line with the view of social desirability as response distortion.…”
Section: Instrument Developmentmentioning
confidence: 75%
“…In a study focusing only on the social-relational SAPI concepts, we found them to be more strongly related to impression management than to lying (lying was in fact positively related to the negative social-relational concepts in a multiple regression analysis; Valchev et al, 2014). The lying aspects of social desirability can be viewed as a purposeful distortion of responses; the impressionmanagement aspects can be viewed as a personality characteristic of effortful selfregulation in an interpersonal context (Uziel, 2010). We examine the associations of all SAPI factors with both types of social desirability.…”
Section: Part 2: Sapi and Social Desirabilitymentioning
confidence: 84%
“…The ubiquitous problem of SDR has led to a scale proliferation (Paulhus, 1991;Uziel, 2010). The scale most commonly used in the past 60 years is the Marlowe-Crowne Social Desirability Scale (MCSDS; Beretvas, Meyers, & Leite, 2002;Crowne & Marlowe, 1964).…”
Section: Articlementioning
confidence: 99%
“…However, according to abundant empirical evidence (Chen, Watson, Biderman, & Ghorbani, 2016;McCrae & Costa, 1986;Uziel, 2010), self-reports of personality traits should not be perceived by design as contaminated with the need of social approval (e.g. because in many studies self-reports satisfactorily correlate with the ratings of others).…”
Section: 00mentioning
confidence: 99%